Recent patterns of vagal nerve stimulator use in the United States: Is there a racial disparity?. (15th March 2019) - Fox, Jonah; Lekoubou, Alain; Bishu, Kinfe G.; Ovbiagele, Bruce
Summary: Objective: Patients with refractory epilepsy are at a high risk of complications but may not receive the same level of care across racial groups. We aimed to ascertain racial inequalities and trends in the use of a vagal nerve stimulator (VNS) among adult patients with refractory epilepsy. Methods: A total of 24 159 adults (18 years and older) with refractory epilepsy from the National Inpatient Sample between the years 2006 and 2014 were included in this analysis. We used a multivariate logistic regression analysis to evaluate independent predictors of VNS use among patients with refractory epilepsy. Covariates included gender, age, insurance type, and household income. In addition, we evaluated for trends in VNS use over the 9‐year period of data collection. Results: A total of 1.56% of patients with refractory epilepsy had used a VNS between 2006 and 2014. Overall, there was a trend of decreased use of a VNS between 2006‐2008 (2.1%) and 2012‐2014 (0.9%). In the adjusted multivariate logistic regression analysis, blacks (odds ratio [OR] = 0.52, 95% confidence interval [CI] = 0.35‐0.77) were significantly less likely to have used a VNS relative to non‐Hispanic whites. Additional factors independently associated with a decreased likelihood of VNS use were age > 65 years (OR = 0.51, 95% CI = 0.28‐0.95) and years 2012‐2014 (OR = 0.44, 95% CI = 0.28‐0.67). Significance: There was a trend toward a decrease in the use of a VNS among adult patients with refractory epilepsy. Our results also suggest that black patients with refractory epilepsy were less likely to receive a VNS independently of other variables. Increased work toward effectively reducing racial disparities in access to quality epilepsy care is crucial.